2022
DOI: 10.1128/spectrum.00251-22
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Antimicrobial Resistance, and Molecular Characterization of Campylobacter Isolated from Broilers and Broiler Meat Raised without Antibiotics

Abstract: Campylobacter is one of the main bacterial pathogens that cause campylobacteriosis in the United States. Poultry is considered a major reservoir for the transmission of Campylobacter to humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 49 publications
1
21
1
Order By: Relevance
“…Thus, additional studies should be conducted to explore more in‐depth the relationship between the pathogenic traits and the antimicrobial resistance in Campylobacter strains. The high distribution of virulence factors was also reported in surveys conducted in the United States (Poudel et al., 2022 ), Poland (Wieczorek et al., 2018 ), Brazil (Takeuchi et al., 2022 ), Pakistan (Melo et al., 2013 ) and China (Zhang et al., 2016 ). We found a higher distribution of virulence factors among the C. jejuni isolates than C. coli bacteria.…”
Section: Discussionsupporting
confidence: 55%
“…Thus, additional studies should be conducted to explore more in‐depth the relationship between the pathogenic traits and the antimicrobial resistance in Campylobacter strains. The high distribution of virulence factors was also reported in surveys conducted in the United States (Poudel et al., 2022 ), Poland (Wieczorek et al., 2018 ), Brazil (Takeuchi et al., 2022 ), Pakistan (Melo et al., 2013 ) and China (Zhang et al., 2016 ). We found a higher distribution of virulence factors among the C. jejuni isolates than C. coli bacteria.…”
Section: Discussionsupporting
confidence: 55%
“…In India, resistance to CIP and ERY reaches values of 33.3 and 21.4% in strains isolated from chicken carcasses [ 31 ]. However, Poudel et al (2022), in China, demonstrated a reduction in the levels of resistance to CIP (from 28% to 15.3%) in isolates from chickens raised without the use of antimicrobials in veterinary practices [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…In total, two endogenous or “housekeeping” genes, plus 20 target genes associated with immune response and D 3 -related activity were identified for RT-qPCR ( Table 1 ). The forward and reverse primers of house-keeping genes (glyceraldehyde-3-phosphate dehydrogenase [ GAPDH ] and 18S ribosomal RNA [ 18S ]); genes related to immunity including interleukin ( IL ) -2 , IL-6 , IL-10 , interferon gamma ( IFN-γ ), myeloid differentiation factor 88 ( MyD88 ), transforming growth factor beta 4 ( TGF-β4 ), Toll-like receptor ( TLR )-4, and TLR-15 ; and genes linked to vitamin D activity including 1α-hydroxylase, 24-hydroxylase, 25-hydroxylase, and VDR were designed according to the procedure described by Fatemi [ 31 ] and Poudel et al [ 32 ]. NormFinder software version 20 was used to normalize the target gene data [ 33 ], and the normalization suitability of the expression of GAPDH and 18S genes were tested.…”
Section: Methodsmentioning
confidence: 99%